EDUCATIONAL ACTIONS FOR THE PREVENTION OF CERVICAL CANCER: DISCOURSE OF QUILOMBOLA WOMEN - Gonçalves De Souza, Thais; Pereira Alves, Beatriz; Lira da Silva, Anna Beatryz; Lunara Alves Barbalho, Isabela; Cristina de Abreu Temoteo, Rayrla; Costa Fernandes, Marcelo (Journal of Health Care, 2022)
Introduction: Cervical Cancer is the third type of cancer that kills women the most, affecting mainly those with lower socioeconomic status and who have difficulties in accessing health services, such as quilombola women. Objective: To understand how health education proposals can contribute to the self-knowledge of quilombola women about cervical cancer prevention. Methods: This is an excerpt from a graduation project in nursing at the Federal University of Campina Grande, carried out in 2019, based on the action-research method and analyzed through the methodological process of the Collective Subject Discourse. Results: After carrying out the situational diagnosis, three meetings were held with the quilombola women, in which knowledge about Cervical Cancer was built and feelings related to the disease were dealt with, using active methodologies associated with the representations and inherent characteristics preventive habits, especially the Pap smear. Conclusions: The educational actions caused a change in the knowledge of women about cervical cancer and its preventive methods, thus showing that educational activities are a possibility for women’s self-knowledge about cervical cancer prevention, making them holders and multipliers of knowledge in their collective reality.